Mutual performance assessment model: Comparative analysis - Zhorifah, Bazfa Azzah; Harjito, Dwipraptono Agus (Asian Management and Business Review, 2021)
This study aims to determine the comparison of mutual funds performance between stock mutual funds, fixed income mutual funds and mixed mutual funds in 2015-2017 using the Jensen, Sharpe, Treynor and Black models. Using purposive sampling method, this study used a sample of 30 mutual funds consisting of 10 equity funds, 10 fixed income mutual funds, and 10 mixed mutual funds during 2015-2017. The data analysis used to test the hypothesis was the One Way ANOVA test and the Kruskal-Wallis test. The results showed that there was no difference in performance between stock mutual funds, fixed income mutual funds, and mixed mutual funds in 2015-2017 which were analyzed using the Jensen, Sharpe, and Treynor models, there was a difference in performance between stock mutual funds, fixed income mutual funds, and mixed mutual funds in 2015. -2017 were analyzed using the Treynor and Black models.